2022
DOI: 10.1039/d2py00185c
|View full text |Cite
|
Sign up to set email alerts
|

The copolymerization of SO2with propylene oxide mediated by organic ammonium salts: a comprehensive study of the main-chain structure, living polymerization character and regioselectivity

Abstract: The utilization of sulfur dioxide (SO2) for constructing sulfur-containing polymers is of much significance in term with either environment issue or obtaining high-valued materials. The copolymerization of SO2 with epoxides...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…To obtain SO 2 -based TPUs, PPS diols with controlled low M n are required. Our previous study revealed that the organic ammonium salt-initiated copolymerization of SO 2 with PO is a living anionic polymerization, allowing for the synthesis of PPS with tunable M n s. 15 In this context, PPS diols with various M n s were obtained by tailoring the feed ratio of the PO/initiator/chain transfer agent (Table S1†). Matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy (MALDI-TOF MS) was used to characterize the structures and end groups of the obtained PPS diols.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain SO 2 -based TPUs, PPS diols with controlled low M n are required. Our previous study revealed that the organic ammonium salt-initiated copolymerization of SO 2 with PO is a living anionic polymerization, allowing for the synthesis of PPS with tunable M n s. 15 In this context, PPS diols with various M n s were obtained by tailoring the feed ratio of the PO/initiator/chain transfer agent (Table S1†). Matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy (MALDI-TOF MS) was used to characterize the structures and end groups of the obtained PPS diols.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 An effective method of managing SO 2 levels is to utilize them in chemical manufacturing (sulfuric acid, sulfuryl chloride, and metal sulfite salts), food preservatives, bleach, synthetic chemistry, and SO 2 -based polymers. 5–19 For the past 80 years, studies on the development of SO 2 -based copolymers have been conducted; SO 2 -based copolymers are obtained from the copolymerization of SO 2 with various monomers via free-radical or ionic polymerization initiated by light or catalysts, 12,20–24 and are widely used in degradable materials, electron beam lithography, positive photoresists, and sulfur cycles. 25–28 Recently, there has been growing attention towards polysulfites (PPSs), an important category of SO 2 -based polymers that are synthesized via the copolymerization of SO 2 and epoxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copolymerization of SO 2 with PO demonstrated high efficiency and high polymer selectivity, thus providing copolymers with perfectly alternating structures. 246 The long-term coexisting polyether linkages in the resultant copolymers were isolated cyclic polyether segments, which resulted from the SO 2 -initiated cationic polymerization with PO. Exploration of the regioselectivity of the SO 2 /PO copolymerization indicated that the ring opening of PO preferred 72 and 25% attacks at the methane and methine carbons, respectively.…”
Section: Copolymerization Of So 2 With Epoxidesmentioning
confidence: 99%
“…Ring-opening of PO preferred a 72% attack at the methene carbon and a 28% attack at the methine carbon. 147…”
Section: Copolymerization Of So2 and Epoxides To Polysulfitesmentioning
confidence: 99%